KORELASI TINGKAT HARGA KARET TERHADAP KESEJAHTERAAN HIDUP KELUARGA PETANI KARET DI DESA LUBUK MANDIAN GAJAH KECAMATAN BUNUT KABUPATEN PELALAWAN - Silaen, Pahala Hendri; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Lubuk Mandian Gajah Village, Bunut Subdistrict, Pelalawan District is one of the rubber-producing areas in Province of Riau and most of the population are livelihoods as rubber farmers who own land and tap their own rubber. This study examines the correlation of rubber price levels to the welfare of rubberfarmer families and the purpose of this study determines the correlation of rubber price levels with the welfare of rubber farmers, the level of rubber prices and the level of welfare of rubber farmers.The process of data collection is done by sharing questionnaires with respondents in a simple / random sampling. The results of the analysis show that there is a correlation between the level of rubber prices and the welfare of rubber farmers, the level of rubber prices in the research location is relatively low with an average price of Rp.6,799 and for the welfare level of 42 respondents, 32 respondents are quite well .Keywords: Attractions , Social, economic.Â Keywords: Rubber Farmer, Welfare, Correlation